Art of communicating : achieving interpersonal impact in business - Decker, Bert (Crisp Pub. Menlo ParkUS, 1996)
Explains the dynamics of effective communication between people, and explores 9 behavioral skill areas that impact on interpersonal communication. Identifies these areas as: eye communication; posture and movement; gestures/facial expression; dress and appearance; voice and vocal variety; language, pauses and non-words; listener involvement; humour; and, the natural self.